Buddhist Discourse in Changing Times: The Significance of Buddhist Magazines in Early 20th-Century Korea with a Focus on Bulgyo - Junghyun Kwon; Jongjin Kim (Religions)
In early 20th-century Korea, Buddhist magazines emerged as vital extra-canonical sources, offering a modern platform that complemented traditional Buddhist texts. These publications navigated the complexities between succeeding Buddhist tradition and embracing modernity, addressing the historical challenges of the 19th century while also contributing to the preservation of national sovereignty and the formation of a modern Korean Buddhist identity. Serving as a forum for scholarly works on Buddhist translation, doctrine, and history, as well as literature, education, and propagation, these magazines became central to both intellectual and spiritual discourse. Of the more than 30 periodicals published during the Japanese occupation, Bulgyo stood out as the longest-running and most influential magazine, with its complete archive preserved. Bulgyo brought together various members of the Buddhist community as both contributors and readers, broadening the scope of Buddhism to include a diverse range of topics such as academia, literature, art, women, and children. This article explores the role and significance of Korean Buddhist magazines during the Japanese colonial period, with a particular focus on Bulgyo, and examines how the publication helped shape Buddhist modernity within Korea’s complex political and religious landscape.